2020
DOI: 10.3390/agronomy10111633
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Strategies to Reduce NH3 Emissions from Slurries in European Agriculture and Consequences for Greenhouse Gas Emissions

Abstract: The intensification of livestock production, to accommodate rising human population, has led to a higher emission of ammonia into the environment. For the reduction of ammonia emissions, different management steps have been reported in most EU countries. Some authors, however, have criticized such individual measures, because attempts to abate the emission of ammonia may lead to significant increases in either methane, nitrous oxide, or carbon dioxide. In this study, we carried out a meta-analysis of experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 59 publications
(140 reference statements)
2
31
0
2
Order By: Relevance
“…Therefore, we stay critical with regard to the results of a meta‐analysis by Emmerling et al. (2020) who concluded that applications of acidified slurry may not result in stimulation of soil N 2 emission, specifically as details of the underlying studies, which were anyhow small in numbers (2–7), are not displayed in detail. However, there is compelling evidence, also observed in our study, that slurry acidification results in higher soil N availability, which is known to promote crop growth for example, of winter wheat, spring barley or maize (Birkmose & Vestergaard 2013; Fangueiro et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, we stay critical with regard to the results of a meta‐analysis by Emmerling et al. (2020) who concluded that applications of acidified slurry may not result in stimulation of soil N 2 emission, specifically as details of the underlying studies, which were anyhow small in numbers (2–7), are not displayed in detail. However, there is compelling evidence, also observed in our study, that slurry acidification results in higher soil N availability, which is known to promote crop growth for example, of winter wheat, spring barley or maize (Birkmose & Vestergaard 2013; Fangueiro et al.…”
Section: Discussionmentioning
confidence: 99%
“…In order to reduce the emissions of NH 3 , different national and international directives are in place (e.g., DEFRA, 2018; Guthrie et al., 2018; United Nations Economic Commission for Europe, 2015) which include practices to mitigate NH 3 losses from agricultural sources. Practices discussed to reduce NH 3 volatilization following slurry application to agricultural lands are dilution of slurries, addition of acids, salts and formalin, direct injection of slurry in the soil or timing of slurry/ manure spreading (Bussink & Oenema 1998; Emmerling et al., 2020; Hou et al., 2015; Seidel et al., 2017; Sommer & Jensen 1994; Velthof et al., 1990; Whitehead & Raistrick 1990). However, practices regarding incorporation of slurry into the soil and better timing of slurry applications in response to plant nutrient demands, for example, via split application, can be cost and time intensive for small farms.…”
Section: Introdctionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nitrous oxide emissions from cropland increase with nitrogen fertilization, but the increase can be mitigated through better compliance with fertilizer recommendations, and the use of nitrification inhibitors and biochar [72]. Slurry acidification, deep placement, and urease inhibitors decreases ammonia emissions from slurries and urea fertilizers applied to soil [76,86]. No meta-analysis studies related to the effectiveness of manure products from different manure processing techniques [87].…”
Section: Nutrient Managementmentioning
confidence: 99%